Analisis Potensi Desa Sebagai Dasar Dalam Peningkatan Pendapatan Asli Desa (PADes) Pada Desa Nebe Kecamatan Talibura Kabupaten Sikka - Riky, Johanes Nong; Sanga, Konstantinus Pati; Lamawitak, Paulus Libu (Universitas Nusa Nipa Maumere, 2025)
This study aims to analyze how the processing of village potential in increasing the original income of the village in Nebe village, Talibura District, Sikka Regency. The research method used is qualitative descriptive with data collection techniques through interviews, observation and documentation. The results of the study show that the management of village potential in Nebe Village has not been running optimally, which has an impact on the lack of increase in Village Original Income (PADes). This can be deduced from four main aspects: namely: The decline in public participation in paying contributions is caused by a lack of transparency and accountability in fund management, Inadequate physical market conditions, such as leaky stalls, irregular aisles, and the lack of facilities such as toilets and parking areas, are the main causes of the decline in revenue from market levies, drinking water depot business units managed by BUMDes do not reach the annual revenue target and shows a downward trend from year to year, and there is a decrease in revenue from tax revenue sharing caused by low public awareness, administrative problems such as duplication of SPPT, and the number of residents from outside the area who are not recorded.